PENDIDIKAN JALAN TENGAH DI KERAJAAN SIAK (1915-1945) - Wilaela Wilaela (Sosial Budaya, 2015)
This research discusses about what and how the educational system during the reign of the Sultan Syarif Kasim II in Siak. The finding of this research shows that after Hindia-Belanda regime opened the lower school such as Hollandsch Inlandsch School, Inlandsch School and Sekolah Desa, then the Sultanate also established some Islamic-based school such as Madrasah Taufikiyah, male school. In fact, his wife also opened some islamic-based school for girls that focused on girl specific skills and Madrasah Anisa. The opening of these schools was a sign showed by the Kingdom that they were not going along with colonialism and also it was percieved as a way to increase the popularity and influence of Siak Kingdom that had gradually decreased. At the end this action was being taken for the sustainability of the Malay Kingdom as the dissemination of Islam and education.